2019
DOI: 10.1109/access.2019.2895776
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Feature Enhancement Method Based on Improved Constraint Model of Online Dictionary Learning

Abstract: Online dictionary learning (ODL) is an emerging and efficient dictionary learning algorithm, which can extract fault features information of fault signals in most occasions. However, the typical ODL algorithm fails to consider the interference of noise and the structural features of the fault signals, which leads to the fault features of weak fault signals that are difficult to extract. For that, a novel feature enhancement method based on an improved constraint model of an ODL (ICM-ODL) algorithm has been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…The flaw of EMD is that its results show the phenomenon of mode aliasing and endpoint effects. The decomposition result of LMD is greatly affected by the step size [16][17][18][19][20]. EEMD is developed on the basis of EMD, it is adaptively decomposed by adding white noise to the original signal and calculate mean of the intrinsic mode function (IMF), but the amplitude of the added white noise has a great influence on its decomposition result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flaw of EMD is that its results show the phenomenon of mode aliasing and endpoint effects. The decomposition result of LMD is greatly affected by the step size [16][17][18][19][20]. EEMD is developed on the basis of EMD, it is adaptively decomposed by adding white noise to the original signal and calculate mean of the intrinsic mode function (IMF), but the amplitude of the added white noise has a great influence on its decomposition result.…”
Section: Introductionmentioning
confidence: 99%
“…respectively by using the formulas (14)-(16). Iterative step (2) until the termination condition is satisfied and finally k IMFs are obtained.…”
mentioning
confidence: 99%
“…Combining advantages of both WT and EMD, the EWT can construct the wavelet basis in an adaptive way and decompose a signal according to the contained information. Therefore, EWT has attracted much attention and been used in a variety of applications, including medicine, biology [21,22], and machinery [23][24][25][26][27][28][29][30][31][32][33]. The traditional spectrum segmentation is achieved by detecting local maxima or minima of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…With constant development of modern industrial technology, fault monitoring of gearbox is more and more valued in research field [1][2][3][4][5][6][7][8][9][10]. As the key component of gearbox, the study of gear fault diagnosis method [11][12][13][14] is of great significance. Meshari et al [15] carried out an extensive study of gearbox fault and found that failure of gear tooth is one of the leading causes of gearbox fault, and that peeling is one of the common gear failures.…”
Section: Introductionmentioning
confidence: 99%